1994
DOI: 10.1159/000244062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Respiratory Stimulants on Cerebral Metabolism and Blood Flow

Abstract: The cerebral metabolic and circulatory effects of the two main classes of respiratory stimulants used in the apnea of the newborn and premature infant, i.e. methylxanthines and doxapram, have not been studied in great detail. In adult animals and humans, methylxanthines widely increase cerebral metabolic rates and simultaneously decrease cerebral blood flow levels. Thus, these compounds are able to reset the level of coupling between cerebral blood flow and energy metabolism inducing a relative hypoperfusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that caffeine, in addition to dopamine, also increases the turnover of other monoaminergic neurotransmitters such as serotonin and noradrenalin (Fredholm et al, 1999) which may play different roles in alcohol and nicotine addiction. Also, effects of caffeine on cerebral glucose utilization (Nehlig, 1986), its central vasoconstrictive effect (Nehlig, 1994) and its other, as yet unknown, actions may contribute to its effect on alcohol and nicotine intake. In conclusion, these preclinical studies with caffeine suggest that adenosine receptor systems in the brain may play an important role in both alcohol and nicotine intake and deserve further preclinical and clinical studies regarding these and other addictions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that caffeine, in addition to dopamine, also increases the turnover of other monoaminergic neurotransmitters such as serotonin and noradrenalin (Fredholm et al, 1999) which may play different roles in alcohol and nicotine addiction. Also, effects of caffeine on cerebral glucose utilization (Nehlig, 1986), its central vasoconstrictive effect (Nehlig, 1994) and its other, as yet unknown, actions may contribute to its effect on alcohol and nicotine intake. In conclusion, these preclinical studies with caffeine suggest that adenosine receptor systems in the brain may play an important role in both alcohol and nicotine intake and deserve further preclinical and clinical studies regarding these and other addictions.…”
Section: Discussionmentioning
confidence: 99%
“…1,250 g is associated with the total dosage and duration of doxapram therapy. However, doxapram is generally considered a drug with a good margin of safety and is widely used in preterm infants [14] . …”
mentioning
confidence: 99%
“…It is therefore possible that the cerebrovascular resistance is slightly higher in nonexperimental settings. However, a counteracting effect of doxapram is possible as mild cerebral vasoconstriction has been reported after its use (27)(28)(29).…”
mentioning
confidence: 99%